Development of LKPD Based on Discovery Learning on Human Respiratory System Material to Train Skills Student Critical Thinking - Fauziah, Siti; Khairuna, Khairuna; Reflina, Reflina (UNDIKMA, 2023)
LKPD (Student Worksheet) based on discovery learning is intended to provide learning knowledge directly in the process of meaningful learning activities so as to direct students to find learning concepts. This study aims to determine the level of feasibility, practicality and effectiveness of LKPD based on Discovery Learning to train students' critical thinking skills on respiratory system material. Researchers used the R&D (Research and Development) method using a 4-D development model (Define, Design, Development and Desemminate) developed by S. Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel in 1974. The test subjects in the study consisted of 36 students from class XI IPA SMA PAB 4 Sampali. The results showed that the feasibility value of developing LKPD from material experts was 86.1% with the very feasible category and LKPD experts by 75% with the feasible category. Then the percentage of practical scores for LKPD development from biology teachers and students of science XI was 82.14% and 83.47% respectively with the practical category. The effectiveness of LKPD development based on individual completeness from the pre-test and post-test students obtained an average N-Gain score of 62.14, so the use of the method has been effective because the N-Gain normality value obtained between 0.30 < g < 0.70 with the